27+x-3X=47=x

Simple and best practice solution for 27+x-3X=47=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27+x-3X=47=x equation:



27+x-3x=47=x
We move all terms to the left:
27+x-3x-(47)=0
We add all the numbers together, and all the variables
-2x-20=0
We move all terms containing x to the left, all other terms to the right
-2x=20
x=20/-2
x=-10

See similar equations:

| 1/4y–3=9 | | -19=47-t | | 7^b=94 | | 49=u+6u | | 9x+5=-25 | | 2^-2k=16 | | 3x-55=23 | | 7x1+18=74 | | 4v+2=-28.4 | | 9+2n=27 | | 3x+47+10-27+x=x | | 7=2n=-3 | | -6(1)-4y=-6 | | 113=999+n | | 0=2(x-7)/7-7(x-2)/2 | | X^2+140x+12800=0 | | 2x+30+2x+54=90 | | 3 = d3− 1 | | 55-n=51 | | 2x+302x+54=90 | | 6z-18=3z | | -4x-6(-9)=16 | | 2x+44=96 | | x^2-8x+16/x^2-16=10/30 | | 180=7x3(-6x+15) | | 27+x-3x+47=10 | | 3/4m+10=40 | | -1/9(z+3)=2/3(z-2/3) | | 18=2j+2 | | 3x-5(x-2)=-8+2x+6 | | y=-3/5(-5)+1 | | -6x-3(-1)=9 |

Equations solver categories